The analysis of polymers for biomedical applications - Rafati, Ali (2011)
The aim of this work was to analyse the surface of biomedically relevant polymers with a range of surface sensitive techniques both in the interest of improving our knowledge of such polymeric delivery systems and the techniques used. Specifically time of flight- secondary ion mass spectrometry (ToF-SIMS) was a focus of this work complemented by a range of supportive surface and bulk analytical techniques. The new technique of X-ray photoelectron spectroscopy (XPS) depth profiling of organics was scrutinised through its application to a thin film blend of poly(l-lactic acid) (PLA) and the analgesic codeine in Chapter 3. Surface depletion of drug was observed in these films and was quantified for the first time with XPS.